Biologi Ikan Baronang Lingkis (Siganus canaliculatus) yang Dominan Tertangkap pada Daerah Pemasangan Bio-FADs di Perairan Tompotana Takalar - Kantun Dananjaya; Andi Yuliani Paris (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
Rabbitfish are used by the community with various types of fishing gear so that it is thought to have resulted in changes in the population. This study aims to analyze the biological aspects of rabbitfish which include the composition of the type of catch, size structure, growth pattern, stages of gonad maturity and the size of the first gonad maturity. The research was carried out from May to July 2021 in the waters of Tompotona, Takalar Regency, South Sulawesi and and was carried out in the installation area of ​​Bio-FADs. Data retrieval was carried out through direct capture using bubu in the morning and afternoon day. The results showed that the catch was 114 fish with S. canaliculatus 99 fish (86.84%) and S. guttatus 15 fish (13.16%). The composition of the dominant species of white-spotted rabbitfish (S. canaliculatus) caught in the morning was 81 fish (81.82%) and 18 fish (18.18%) afternoon. The structure size of the white-spotted rabbitfish caught in the morning ranged from 11.63-27.97 cm (17.70 ± 3.35 cm) and in the afternoon ranged from 10.54-26.94 cm (19.05 ± 3.16 cm). The type of growth caught in the morning and evening was negative allometric (b<3). The level of gonad maturity obtained from the immature stage to gonad maturity. The size of the first gonad maturity in the morning catch was 20.26 cm and in the afternoon was 17.98 cm.